Morphometric analysis of glomeruli, clinical features and outcome in obese and non-obese patients with focal segmental glomerulosclerosis patients - Jordanova, Elena Angel; Janković, Radmila; Naumović, Radomir; Ćelić, Dejan; Ljubičić, Bojana; Simić Ogrizović, Sanja; Basta Jovanović, Gordana (Vojnosanitetski pregled, 2021)
Background/Aim. In the past three decades, focal segmental glomerulosclerosis (FSGS) was commonly regarded as a part of obesity-related glomerulopathy (ORG), a distinct entity featuring proteinuria, glomerulomegaly, progressive glomerulosclerosis, and a decline of renal function. The present study aimed to evaluate the glomerular morphometry, clinical features, and a two-year outcome in the obese and non-obese FSGS patients. Methods. The study included 35 FSGS patients (23 males, aged 46.5 ± 15.2 years) divided into two groups: obese [body mass index (BMI) ≥ 27 kg/m2 (18 patients, aged 47.2 ± 15.5 years)] and non-obese [BMI
Keywords: biopsy; glomerular filtration rate; glomerulosclerosis, focal segmental; kidney glomerulus; obesity; risk assessment; treatment outcome